Antioxidant activity of phlorotannins from brown algae - Liu, Xin; Yuan, Wenqiao; Sharma-Shivappa, Ratna; van Zanten, John (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: The antioxidant activity of the phlorotannins extracted from five marine algae species (Saccharina latissima, Alaria esculenta, Laminaria digitata, Fucus vesiculosus and Ascophyllum nodosum) was studied. Three phlorotannin groups, including soluble, membrane-bound, and extracted membrane-bound phlorotannins obtained by two solvent extraction methods were investigated for their DPPH radical scavenging activity. F. vesiculosus and A. nodosum showed the highest phlorotannin yield (14.83 mg-extract/g-algae and 12.80 mg-extract/g-algae, respectively) among the five algae species. Their soluble phlorophannin (SP), membrane-bound phlorotannin (MP) and extracted membrane-bound phlorotannin (eMP) extracts all showed equal or greater DPPH radical scavenging activity than the commercial antioxidants of butylated hydroxytoluene and ascorbic acid. The antioxidant potential that combines phlorotannin yield and antioxidant activity of the MP extracts of F. vesiculosus and A. nodosum (5890 mL/g and 5278 mL/g algae, respectively) were higher than those of SP and eMP, suggesting that the MPs of F. vesiculosus and A. nodosum had great potential to be used as antioxidants. Different extraction methods also showed significantly different effects on the antioxidant activity of the phlorotannin extracts.Keywords: brown algae, phlorotannin, antioxidant activity, antioxidant, bioseparation, polyphenol, solvent extraction methodsDOI: 10.25165/j.ijabe.20171006.2854Citation: Liu X, Yuan W Q, Sharma-Shivappa R, van Zanten J. Antioxidant activity of phlorotannins from brown algae. Int J Agric & Biol Eng, 2017; 10(6): 184–191.